AGENT-BASED MODELING TO EXPLORE THE IMPACT OF SNAIL CONTROL, DIAGNOSTIC METHODS AND MASS DRUG ADMINISTRATION ON SCHISTOSOMIASIS ELIMINATION - Vilches, Thomas Nogueira [UNESP]; Rubio, Felipe Alves; Souza, Renata Perotto de; Graeff-Teixeira, Carlos (World Scientific Publishing, 2025)
In this paper, we present an agent-based model to simulate the transmission of schistosomiasis infections within a human population that accounts for the miracidium and cercariae reservoirs and the snail population in order to verify the efficacy of “test-and-treat” strategy as compared to mass drug administration and snail control. To do that, we used data about prevalence from the district of Candeal, in Estancia-SE, Brazil. We used a genetic algorithm to fit the unknown parameters of the model and analyze the diagnosis-based control strategies. We found that either individual or mass drug administration, must be combined to snail-population reduction to effectively control schistosomiasis. The diagnostic-based treatment, in the case with snail-population control, is as effective as the mass drug administration, emphasizing the importance of development of efficient diagnosis methods.